2021
DOI: 10.52462/jlls.122
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive language of ‘Thai SELECT Premium’ restaurant menus: Appealing perception and collocations

Abstract: The study examined menu descriptions of Thai restaurants on how appealing the menus communicated with customers. Data were taken from restaurant websites with 'Thai SELECT Premium' certifications in the UK. 673 menu items were obtained and analyzed in five categories (nationalism, characteristics, sensory cues, branding, organic and healthy concerns). Sensory cues category was mostly used (68.95%) followed by characteristics (41.9%) and nationalism 17.53%). Six Thai dishes on CNN Travel World's 50 Best Foods l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…For example, previous studies in the literature showed that restaurants could use carbon labels (a form of extrinsic cue) to encourage consumers to purchase more environmentally friendly food options [20]. It may also be possible for restaurants to use certain cue words to effectively highlight a locally grown menu item since words could shape customers' knowledge and perceptions [21]. However, the list of cue words for locally grown food is exhaustive [9,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous studies in the literature showed that restaurants could use carbon labels (a form of extrinsic cue) to encourage consumers to purchase more environmentally friendly food options [20]. It may also be possible for restaurants to use certain cue words to effectively highlight a locally grown menu item since words could shape customers' knowledge and perceptions [21]. However, the list of cue words for locally grown food is exhaustive [9,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%